Coping with singleness - Shakiba Pourasad Shahrak; Serge Brand; Ziba Taghizadeh (BMC, 2023)
Abstract Background The number of never-married women is increasing worldwide. According to a recent census (2016) this trend is also apparent in Iran. The aim of the present study was to investigate how never-married Iranian women cope with their single status. Methods The present study was qualitative in nature. Purposeful sampling with maximum variation was used to select 18 never-married women aged over 35. Data were analyzed on the basis of conventional content analysis and inductive reasoning. Results One hundred fifty-four codes, nine subcategories, three categories, and one theme were extracted. The three categories were: (1) responding to sexual needs (sub-categories: having sex; masturbation; sexual abstinence); (2) responding to emotional needs (sub-categories: getting used to being alone; living with family; closer relationship with good friends); (3) lifestyle changes (subcategories: accepting God's destiny; striving for beauty and health; becoming absorbed in work and education). Conclusions Results showed that never-married women aged over 35 tried to adapt to sexual and emotional needs and lifestyle changes as proxies of singleness in various ways. It appears that these women adopted several strategies to cope with the lack of a spouse, children, or family life, these normally being developmental tasks characteristic of early adulthood.